2022
DOI: 10.1097/gox.0000000000004054
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Digital Defects with the Free Proximal Ulnar Artery Perforator Flap

Abstract: Background:The aim of post-traumatic digital reconstruction is to restore form and function, allowing early rehabilitation. In the absence of feasible local options, free tissue transfer can be a versatile and reliable alternative. The aim of this study was to describe our experience with the use of the free proximal ulnar artery perforator flap (PUPF). Methods: Our prospectively maintained free flap database was inquired for patients that had undergone digital reconstructions with free PUPFs. Results: Six pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…The PUPF’s main disadvantage is the perforator’s small diameter, which demands precise supermicrosurgical abilities to complete the anastomosis, as well as the flaps’ diameter, which, when larger than 6 cm, is mostly impossible to close the donor site, possibly requiring grafting. 17 In our study, no complications were observed in the long-term follow-up (Fig. 3 ).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…The PUPF’s main disadvantage is the perforator’s small diameter, which demands precise supermicrosurgical abilities to complete the anastomosis, as well as the flaps’ diameter, which, when larger than 6 cm, is mostly impossible to close the donor site, possibly requiring grafting. 17 In our study, no complications were observed in the long-term follow-up (Fig. 3 ).…”
Section: Discussionsupporting
confidence: 43%
“…In this study, the PUPF was the second most commonly used flap; based on the perforator of the ulnar artery, it was employed in 13.9% of our small defect repair interventions (the surgical technique employed to harvest the flap is well described in a previous article). 17 The PUPF also has been used to cover digits but with larger defects, mostly when two adjacent fingers were injured, covering both defects and performing the syndactyly release in the second intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Local flaps, such as homodigital and heterodigital flaps, [7][8][9][10] pedicled hand and forearm flaps, or thin free flaps, 11,12 are commonly used to replace the loss of substance. However, these procedures do not restore the injured finger's original length and tissue complexity, resulting in poor functional and cosmetic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, to the defect, flaps harvested from different areas of the body may be employed. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] As in all body surfaces, the viability of reliable recipient vessels is essential in reconstructive surgery. Different from the volar aspect of the hand, there is only one main vessel in the hand dorsum, namely the radial artery (RA).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, to the defect, flaps harvested from different areas of the body may be employed. 1 14 …”
Section: Introductionmentioning
confidence: 99%